Teresa Santander Rodríguez, Escolares médicos en Salamanca (siglo XVI), Salamanca, 1984, 439 pp. + 3 láminas ISBN 84-7481-098-1 (Minerva. Revista de Filología Clásica, 2019)
Reseña de Teresa Santander Rodríguez, Escolares médicos en Salamanca (siglo XVI), Salamanca, 1984, 439 pp. + 3 láminas ISBN 84-7481-098-1